Teachers’ perspectives on barriers and motivators to physical activity participation in children from ethnic minority groups in Newcastle upon Tyne: A qualitative study - Joyce Ene Omenyo Omojor-Oche; Gavin Daniel Tempest; Florentina Hettinga; Kandianos Emmanouil Sakalidis (PLoS ONE, 2026)
Physical inactivity among children in Western countries, especially children from ethnic minority groups, is a global health concern. Schools provide an ideal setting to address children’s physical activity needs, with teachers playing a major role. Therefore, the aim of this study was to explore teachers’ perspectives on barriers and motivators to physical activity participation in children from ethnic minority groups and to determine through their suggestions, how schools can be better supported to provide a physical activity-enabling environment. A purposive sample of eight primary school teachers in the Northeast of England, United Kingdom, participated in semi-structured interviews conducted through a combination of face-to-face and virtual settings. Reflexive thematic analysis identified seven barriers and nine motivators to physical activity, distributed across different levels of the socio-ecological theory. At the intrapersonal level, motivators included fun and wellbeing, whereas barriers included behavioural issues, and increased screen time. The interpersonal level encompassed influences of friends, parents, and teachers. At the institutional level, in-school activities were identified as motivators. At the community level, environmental influence and perceptions of safety were identified as barriers. At the public policy level, government/local council and resources were identified as both barriers and motivators. Notably, the teachers’ perspectives align with previous findings on barriers and motivators to physical activity among children from ethnic minority groups in the Northeast of England, while contributing to policy-level insights. These policy-level insights highlight the importance of staff training, government funding, and sports infrastructure improvements.